Recursos didácticos informáticos aplicados en el proceso de enseñanza aprendizaje a estudiantes de octavo año de educación básica del Colegio Nacional en Ciencias Juan Montalvo provincia de El Oro 2012. - Sarango Tinoco, Jessica Elizabeth (2013)
Technological development has allowed the use of new methodological strategies that bring the use of computerized teaching resources in the teaching process in all areas of knowledge. The problem encountered in this institution of non-use of computerized teaching resources allowed us to present a proposal to solve all the problems in terms of this academic problem.